An RCT with the combination of varenicline and bupropion for smoking cessation: clinical implications for front line use. (29th May 2018) - Cinciripini, Paul M.; Minnix, Jennifer A.; Green, Charles E.; Robinson, Jason D.; Engelmann, Jeffrey M.; Versace, Francesco; Wetter, David W.; Shete, Sanjay; Karam‐Hage, Maher
Abstract: Background and Aims: Despite the availability of several efficacious smoking cessation treatments, fewer than 25% of smokers who quit remain abstinent 1 year post‐treatment. This study aimed to determine if varenicline and bupropion combination treatment would result in higher abstinence rates than varenicline alone. Design: A double‐blind, randomized, parallel‐group smoking cessation clinical trial in which participants were exposed to 12 weeks of treatment and followed for 12 months. Setting: Hospital‐based out‐patient clinic in Texas, USA specializing in cancer prevention. Participants: A total of 385 community smokers (58.44% male) who smoked 1 pack of cigarettes/day [mean = 19.66 cigarettes/day, standard deviation (SD) = 9.45]; had average carbon monoxide (CO) of 26.43 parts per million (SD = 13.74); and were moderately dependent (Fagerström Test for Cigarette Dependence = 4.79; SD = 2.07). Interventions and comparator: Smokers were randomized in a 3 : 1 (active: Placebo) ratio to 12 weeks of treatment as follows: placebo ( n  = 56), varenicline (Var; n  = 166), and varenicline + bupropion (Combo; n  = 163). Measurements: A priori primary outcome: prolonged abstinence at 12 months. Secondary outcomes: 7‐day point prevalence abstinence and continuous abstinence; all abstinence measures at end of treatment and 6‐month follow‐ups. Findings: Intention‐to‐treat analysis: the Combo group ( n  = 163) failed to demonstrate superiority to the Var group ( n  = 166) for prolonged abstinence at 12 months [odds ratio (OR) = 0.91, 95% confidence interval (CI) = 0.50–1.64], supported by Bayes factor = 0.06. Both the Var (OR = 6.66, 95% CI = 1.61–59.27) and Combo groups (OR = 6.06, 95% CI = 1.45–54.09) demonstrated superiority to the Placebo group ( n  = 56; score = 8.38, P  < 0.016). Conclusions: The addition of bupropion to varenicline treatment does not appear to increase smoking abstinence rates above that of varenicline alone. The findings support previous research showing a consistently favorable effect of both varenicline and the combination of varenicline and bupropion on smoking cessation compared with placebo.